INTRODUCTION OF PROBLEM METHODS AND TECHNOLOGIES FOR TEACHING PHYSICS - Ashirov Shamshiddin; Boymirov Sherzod; Mamatov Abdurayim; Urozbokov Alijon (International Engineering Journal For Research & Development, 2020)
General secondary school has revealed the shortcomings and inadequacy of solutions in pedagogical processes using problematic methods of teaching physics at school. The article also discussed the introduction of problematic teaching technologies at the Department of electrodynamics of physics, as well as additional recommendations and directions. The Department of electrodynamics of physics also began to differ in the features of problem-based teaching in contrast to other departments.